2017
DOI: 10.1149/07522.0035ecst
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of Li-Oxygen Batteries

Abstract: In this article we develop a mathematical model and analyze the variability of discharge characteristics and impedance spectra in Li-air batteries with organic electrolyte. These batteries are well known to display a large variability of their characteristics from battery to battery (particularly of their specific capacity, energy and power densities), however, the exact reasons of this variability are still under investigation. Our model shows that the intrinsic variability of the pore microstructure which in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…On the modeling side, the common approach to study Li–O 2 batteries is to use continuum models and to capture the effects of pores interconnectivity via a tortuosity factor. The tortuosity is usually described via the Bruggeman relationship, which oversimplifies the role of pore sizes and connectivity on transport. Recently, Mehta et al showed, for the first time, that the local variation of porosity and carbon surface area (CSA) in the cathode can lead to variations in performance as well . In their model, the positive electrode is discretized into fine meshes, and each mesh is assigned slightly different porosity and CSA values.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the modeling side, the common approach to study Li–O 2 batteries is to use continuum models and to capture the effects of pores interconnectivity via a tortuosity factor. The tortuosity is usually described via the Bruggeman relationship, which oversimplifies the role of pore sizes and connectivity on transport. Recently, Mehta et al showed, for the first time, that the local variation of porosity and carbon surface area (CSA) in the cathode can lead to variations in performance as well . In their model, the positive electrode is discretized into fine meshes, and each mesh is assigned slightly different porosity and CSA values.…”
mentioning
confidence: 99%
“…17−19 Recently, Mehta et al showed, for the first time, that the local variation of porosity and carbon surface area (CSA) in the cathode can lead to variations in performance as well. 20 In their model, the positive electrode is discretized into fine meshes, and each mesh is assigned slightly different porosity and CSA values. The porosity and CSA values are chosen based on the overall properties and standard deviations at the macroscopic level.…”
mentioning
confidence: 99%
“…The detailed description of the transport model and the boundary conditions at anode and cathode can be found in Supporting Information. The EIS spectra were computed using the technique presented in ref 35. We assumed a small-signal harmonic perturbation of the discharge current i ̃ejωt where i ̃is the complex magnitude and ω is the angular frequency of the signal and computed the small-signal response of the cell voltage, vẽ jωt , numerically.…”
Section: LImentioning
confidence: 99%